2009 IEEE/WIC/ACM International Joint Conference on Web Intelligence and Intelligent Agent Technology 2009
DOI: 10.1109/wi-iat.2009.175
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Algorithm for Solving Dynamic Complex DCOP Problems

Abstract: Multi Agent Systems and the Distributed Constraint Optimization Problem (DCOP) formalism offer several asynchronous and optimal algorithms for solving naturally distributed optimization problems efficiently. There has been good application of this technology in addressing real world problems in areas like Sensor Networks and Meeting Scheduling. Most of these algorithms however exploit static tree structures and are thus not well suited to modeling and solving problems in rapidly changing domains. Also, while i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…In these, studies agents are in control of a set of different elements such as traffic lights on crossroads [ 63 , 65 ] or platforms from railway systems [ 64 ], where dynamics are represented as the variations in the traffic density from circulating vehicles. Other scenarios were Dynamic DCOPs are modelled include collective autonomous vehicles for collision avoidance [ 66 ], human resources reorganisation such as scheduling elective surgery for emergencies in hospitals [ 67 ], distributed controlling of IoT devices and sensors for minimisation of energy consumption in smart homes [ 47 ], and dynamic social simulation through law enforcement problems and market-based mechanisms for dynamic task allocation to agents [ 68 ]. Proposals without scenarios [ 24 , 25 , 39 , 40 , 42 , 43 , 44 , 53 , 54 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ] are the majority of the studies found.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these, studies agents are in control of a set of different elements such as traffic lights on crossroads [ 63 , 65 ] or platforms from railway systems [ 64 ], where dynamics are represented as the variations in the traffic density from circulating vehicles. Other scenarios were Dynamic DCOPs are modelled include collective autonomous vehicles for collision avoidance [ 66 ], human resources reorganisation such as scheduling elective surgery for emergencies in hospitals [ 67 ], distributed controlling of IoT devices and sensors for minimisation of energy consumption in smart homes [ 47 ], and dynamic social simulation through law enforcement problems and market-based mechanisms for dynamic task allocation to agents [ 68 ]. Proposals without scenarios [ 24 , 25 , 39 , 40 , 42 , 43 , 44 , 53 , 54 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ] are the majority of the studies found.…”
Section: Resultsmentioning
confidence: 99%
“…Other scenarios were Dynamic DCOPs are modelled include collective autonomous vehicles for collision avoidance [ 66 ], human resources reorganisation such as scheduling elective surgery for emergencies in hospitals [ 67 ], distributed controlling of IoT devices and sensors for minimisation of energy consumption in smart homes [ 47 ], and dynamic social simulation through law enforcement problems and market-based mechanisms for dynamic task allocation to agents [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Beyond these first solutions, DCOP algorithms have already been tested in practical scenarios such as travel optimization ( [6], [15]) or planning ( [7]). Among the DCOP algorithms, three are particularly well known: ADOPT [12], DPOP [14], OptAPO [10].…”
Section: Related Workmentioning
confidence: 99%
“…Both variants are based on a mediator agent, so the resolution is not fully distributed. [7] proposed another algorithm to solve dynamic problems called DCDCOP (Dynamic Complex DCOP) based on a case study of time use optimization in a medical context. This algorithm -mainly based on the addition of a Degree of Unsatisfaction measure -dynamically guides agents through the resolution process.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation